ChemInform Abstract: Synthesis of Ramirez Ylides from Morita—Baylis—Hillman Adducts of α‐Bromocinnamaldehyde: An Intramolecular 1, 6‐Conjugate Addition of Phosphorus Ylide. Issue 44 (15th October 2015) - Kim, Ko Hoon; Lee, Sangku; Lee, Junseong; Kim, Jae Nyoung
Abstract In situ generated phosphorous ylides undergo intramolecular 1, 6‐conjugated addition to form Ramirez ylides in often excellent yields.